2007
DOI: 10.1007/s11255-006-9050-4
|View full text |Cite
|
Sign up to set email alerts
|

Serum, urinary and stone zinc, iron, magnesium and copper levels in idiopathic calcium oxalate stone patients

Abstract: Many theories have been put forward to explain the mechanism of stone formation and growth. The aim of this study was to investigate the urinary, serum and stone levels of zinc, iron, magnesium, and copper in patients with calcium oxalate stones and to investigate urinary and serum element levels in healthy controls and to find a possible connection between the elements and calcium oxalate stone formation. A total of 104 patients with calcium oxalate stones ranging in age from 3 to 79 years (mean 44.0 +/- 18.1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
64
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(72 citation statements)
references
References 20 publications
6
64
1
Order By: Relevance
“…[22] Zinc is thought to be an inhibitor of kidney stone formation, but it could also be present in calcium-containing stones. [23] Atakan et al [24] found lower serum and urine zinc levels in patients who previously had stones when compared with stone-free population. Their results indicated that zinc has an inhibitory role in stone formation.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…[22] Zinc is thought to be an inhibitor of kidney stone formation, but it could also be present in calcium-containing stones. [23] Atakan et al [24] found lower serum and urine zinc levels in patients who previously had stones when compared with stone-free population. Their results indicated that zinc has an inhibitory role in stone formation.…”
Section: Discussionmentioning
confidence: 98%
“…Although it is considered by some authors to be one of the most important inhibitors of lithogenesis, [22,24] this is a controversial issue due to conflicting results. [28] Moreover, its inhibitory role in this process has not been clearly explained.…”
Section: Discussionmentioning
confidence: 99%
“…Zinc accounts for the majority of the heavy metals in calcium-based kidney stones [5], and is present in both stone nucleus and the crust [17]. It has been suggested from correlative studies that zinc acts as an inhibitor of kidney stone formation in humans [8,10]. However, results from other studies contradict these findings.…”
Section: Discussionmentioning
confidence: 99%
“…Animal studies have also shown that zinc administration significantly reduced calcium and oxalate deposition in the renal papilla [7]. Atakan et al [8] studied a total of 104 calcium oxalate stone formers and 77 normal controls, and found that stone formers had significantly lower serum and urine zinc levels compared to normal controls, indicating a possible inhibitory role of zinc on stone formation. However, other studies have failed to support this finding [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…However, urinary stones also contain other minor or trace elements due to their natural occurrence in urine. Many researchers dealt with investigation of trace elements in urinary stones in relation to kidney stones formation (Atakan et al 2007;Durak et al 1992;Perk et al 2002; Electronic supplementary material The online version of this article (doi:10.1007/s10653-015-9691-2) contains supplementary material, which is available to authorized users. Slojewski et al 2010;Carpentier et al 2011;Abboud 2008b, c); however, conclusions from such investigations are ambiguous and often contradictory (Slojewski 2011).…”
Section: Introductionmentioning
confidence: 99%